Inequality of Opportunity in Sub-Saharan Africa - Brunori, Paolo; Palmisano, Flaviana; Peragine, Vito (World Bank, Washington, DC, 2016)
In the last decades, inequality of opportunity has been extensively studied by economists on the assumption that, in addition to being normatively undesirable, it can be related to low potential for growth. This paper evaluates inequality of opportunity and the different sources of unequal opportunities in 11 Sub-Saharan Africa countries. The results indicate that the portion of total inequality that can be attributed to exogenous circumstances -- that is, circumstances outside the control of individuals control -- is between 30 percent and 40 percent in the countries considered. The results also indicate a positive association between total consumption inequality and inequality of opportunity. Finally, this paper addresses a number of methodological issues that typically arise when measuring inequality of opportunity with imperfect data, which is the typical case in developing countries.